Miss O'Dell : my hard days and long nights with the Beatles, the Stones, Bob Dylan, Eric Clapton, and the women they loved - O'Dell, Chris, 1947-; Ketcham, Katherine, 1949- (New York : Touchstone, 2009)
The remarkable story of an ordinary woman who lived the dream of millions -- to be part of rock royalty's trusted inner circle. Illustrated with private photographs and jam -packed with intimate anecdotes, Miss O'Dell is a backstage pass to some of the most momentous events in rock history
Derek Taylor -- Ciro's -- Apple -- Lunch at the Aretusa -- James Taylor -- First session -- The lady is a champ -- Ireland -- Savoy truffle -- Hells Angels -- Up on the roof -- The Isle of Wight -- Leon -- Pisces Apple lady -- Hummingbird -- Flying away -- Friar Park -- Pattie's birthday party -- Hare Krishna -- Back to Apple -- Eric and the Dominos -- Miss O'Dell -- Bangladesh -- The Rolling Stones -- The Stones tour -- Too many sunrises -- Maureen -- Christmas in England -- Ringo -- CSNY reunion tour -- Jamaica -- George's tour -- Santana -- Rolling thunder -- Dancing with Dylan -- Pattie's wedding -- Lost years -- Aristocracy -- William
Includes index
Keywords: O'Dell, Chris, 1947-; Sound recording industry -- Employees -- Biography; Rock musicians -- Anecdotes; Concert tours -- Anecdotes